Kontribusi Aliansi Ulama Madura (AUMA) dalam Merespons Isu Keislaman dan Keumatan di Pamekasan Madura - Abd A'la; Ahwan Mukarrom; Mukhammad Zamzami (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
This article analyzes the contributions of the kiais who are members of the Aliansi Ulama Madura (AUMA) in responding to Islamic and publicity issues in the Pamekasan region. This organization was born after the stagnation of the Badan Silaturahmi Ulama Pesantren Madura (BASSRA) organization in guarding the issues of religiousness and Islam. They are committed to fighting for Islamic da‘wah which is k?ffah; an agenda to optimize the concept of amr ma‘r?f nahy munkar collectively and sincerely in order to uphold the motto of the development of Pamekasan based on Islam. In the field of Islam, their vision is to anticipate and avoid Indonesia, especially the Madurese, from all kinds of deviations of teachings and religious beliefs, both Sh?‘ah, Wahabi, Liberal, and Blasphemy (SYIBILIP). Not only in the field of Islam, but this organization also contributes in the political sphere. This can be referred to the strategic roles and functions of those who actively involve themselves in many political dynamics, both at the regional and central levels. At the regional level, the political roles and strategic functions of these organizations are clearly illustrated in the political cooperation they build with elite political parties at the regional level. While at the national level, the strategic role of this organization is indicated by their involvement in national leadership contestation. [Artikel ini menganalisis kontribusi para ulama yang tergabung dalam wadah Aliansi Ulama Madura (AUMA) dalam merespons isu keislaman dan keumatan di wilayah Pamekasan. Organisasi ini lahir pasca mandeknya organisasi Badan Silaturahmi Ulama Pesantren Madura (BASSRA) dalam mengawal isu keumatan dan keislaman. Mereka berkomitmen memperjuangkan dakwah Islam k?ffah; sebuah agenda menjalankan amr ma‘r?f nahy munkar secara kolektif dan demi menegakkan jargon pembangunan Pamekasan yang berasaskan Islam. Dalam bidang keislaman, visi mereka adalah mengantisipasi dan menghindarkan Indonesia, khususnya masyarakat Madura, dari segala ragam deviasi ajaran dan paham kegamaaan, baik Sh?‘ah, Wahabi, Liberal, dan penistaan agama (SYIBILIP). Tidak hanya bidang keislaman, AUMA juga bergerak di wilayah politis. Hal ini dapat dirujuk pada peran dan fungsi strategis mereka yang aktif melibatkan diri dalam banyak dinamika politik, baik di level daerah maupun pusat. Di level daerah, peran dan fungsi strategis politik organisasi ini terilustrasi secara jelas dalam kerja sama politik yang mereka bangun bersama elit partai politik di tingkat daerah. Sedangkan di level nasional, peran strategis organisasi ini mereka tunjukkkan melalui keterlibatan diri dalam kontestasi kepemimpinan nasional.]